2019
DOI: 10.1002/adfm.201907964
|View full text |Cite
|
Sign up to set email alerts
|

Light Detection in Open‐Circuit Voltage Mode of Organic Photodetectors

Abstract: Organic photodetectors (OPDs) are promising candidates for next‐generation light sensors as they combine unique material properties with high‐level performance in converting photons into electrical signals. However, low‐level light detection with OPD is often limited by device dark current. Here, the open‐circuit voltage (Voc ) regime of OPDs is shown to be efficient for detecting low light signals (<100 µW cm−2). It is established that the light‐dependence of Voc exhibits two distinct regimes as function of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“…Previously, we have shown that rubrene can efficiently function as an OPV and OLED with sub-bandgap turn-on voltage and able to detect ultralow light signals when combined with a suitable acceptor, such as fullerene-C 60 . [13,14,15] The origin of the multifunctional diode response of these chromophores has now been linked to arise due to the delicate interplay between singlet excitons, charge transfer states and triplet excitons. [16,17,18] This has led to research into a new class of organic optoelectronic devices, as opposed to their complete reliance on singlet excitons where the formation of triplet excitons has traditionally…”
Section: Multifunctional Diode Operation Of Tetracene Sensitized Polymentioning
confidence: 99%
“…Previously, we have shown that rubrene can efficiently function as an OPV and OLED with sub-bandgap turn-on voltage and able to detect ultralow light signals when combined with a suitable acceptor, such as fullerene-C 60 . [13,14,15] The origin of the multifunctional diode response of these chromophores has now been linked to arise due to the delicate interplay between singlet excitons, charge transfer states and triplet excitons. [16,17,18] This has led to research into a new class of organic optoelectronic devices, as opposed to their complete reliance on singlet excitons where the formation of triplet excitons has traditionally…”
Section: Multifunctional Diode Operation Of Tetracene Sensitized Polymentioning
confidence: 99%
“…Organic materials have attracted tremendous attention due to various advantages such as their low manufacturing costs, low-temperature processability, intrinsic mechanical flexibility, and diversified band gap selection through molecular design. , Organic single crystals present highly ordered molecular packing, absence of grain boundaries, and extremely low defect density, which make them an ideal platform for both the fundamental research and potential applications. Rubrene is a typical organic semiconductor with a herringbone packing arrangement and has been widely exploited in high-performance field-effect transistors, , flexible strain sensors, and phototransistor memories, , due to its high carrier mobility, intrinsic mechanical flexibility, and excellent absorption .…”
Section: Introductionmentioning
confidence: 99%
“…The rise time (t r ) and fall time (t f ) of transient photocurrent are defined as the time for photocurrent raising from 10% to 90% of the maximum photocurrent and the time for photocurrent decreasing from 90% to 10% of the maximum photocurrent. [36] The t r and t f of PM-PPDs with F 6 TCNNQ in active layers are estimated to be 16.3 and 56.7 ms, respectively, which are shorter than the corresponding values of 27.7 and 85 ms for PM-PPDs without F 6 TCNNQ in active layers. The increased response speed of PM-PPDs with F 6 TCNNQ in active layers should be due to the enhanced hole mobility.…”
Section: Resultsmentioning
confidence: 77%